Education in the Digital Age: Navigating Challenges and Cultivating Character Values for the Next Generation - Rosyid Ainur; Kenzaky Mohamad (Indonesian Journal of Education and Social Studies, 2022)
This research aims to discover the challenges of education in the era of society 5.0: strengthening the character values of the digital generation to strengthen the character values of the digital generation so that they can improve the quality of good character. This research was conducted using a qualitative case study approach. This research was conducted at the SMAI Miftahul Afkar Institute under the auspices of the Annabrowi Islamic boarding school, Sidopekso village, Kraksaan, Probolinggo, East Java. The data analysis technique in this research uses the Miles and Huberman data analysis model with stages of data reduction, data display, and conclusion. The research results show that strengthening character values is carried out in several strategies, including instilling character values in every learning activity, optimizing school collaboration with parents, and strengthening character values. The implications obtained from strengthening the character values of the digital generation are that schools have good-quality students and identities that are easily recognized by the public and have student graduates with high character.